The influence of scapular orientation on the medial scapula corpus angle in snapping scapula syndrome - Brittany Percin, BS, MS4; Joseph Featherall, MD; Robert Z. Tashjian, MD; Peter N. Chalmers, MD; Christopher D. Joyce, MD; Alexander J. Mortensen, MD; Heath B. Henninger, PhD (JSES International)
Background: Snapping scapula syndrome (SSS) can result in crepitus and painful scapulae during motion and may be treated with bursectomy and/or superomedial angle resection. The medial scapula corpus angle (MSCA) measures blade curvature on a transverse plane below the suprascapular fossa and may indicate SSS, yet a large overlapping range in MSCA exists between patients with and without SSS. This study quantified the effects of 3-dimensional scapula orientation in the imaging field, and the resulting variability in scapula type and MSCA. Methods: Computed tomography scans from 10 healthy controls (non-SSS) and 8 SSS patients were used to create 3-dimensional scapula models. The scapula type and MSCA were measured on a controlled reference imaging plane, and ones translated and rotated below the supraspinatus fossa to create 19 planes simulating variations due to scapulothoracic orientation. Planes translated and rotated above the reference plane also generated 13 modified MSCA planes to test areas modified during surgical resection. Statistical analyses compared the scapula type and MSCA between the reference and alternate planes within groups. Results: Scapula type commonly changed and the MSCA varied up to 104° within a subject depending on the imaging plane, regardless of location below or above the reference plane. Numerous statistical differences were detected in MSCA between the reference plane and those translated and rotated below that plane in both non-SSS and SSS groups. Planes translated above the reference plane showed consistent statistical differences in MSCA to the reference plane, but only in the SSS group. Discussion: Although scapula type and MSCA were previously shown to differentiate patients, the effect of viewing perspective was not considered. Differences in scapula orientation relative to the imaging plane dramatically varied the scapula type and MSCA, far exceeding differences between groups described previously. Herein, scapula type and MSCA often differed in planes translated above the reference plane, suggesting that scapular abnormalities contributing to SSS are largely at or close to the superomedial angle. Conclusion: The MSCA as defined previously likely lacks the sensitivity and specificity to reliably be used as a clinical diagnostic tool for SSS. The blade showed consistent differences when translated above the reference plane; however, it was still highly variable. Sensitivity and specificity of planes above the reference plane should be investigated further as they may provide reliable differentiation of non-SSS and SSS patients.